ANALYSIS OF THE NEED FOR DEVELOPMENT OF ISLAMIC E-MODULE IN MATRIX MATERIAL IN CLASS XI MA - Prabowo, Restu; Maimunah, Maimunah; Roza, Yenita (Jurnal Pendidikan Matematika dan IPA, 2022)
The problems that often become student complaints are the difficulty of understanding the abstract problems provided in school-facilitated textbooks, in learning mathematics not all teachers connect the material being taught with contextual problems that exist around students, and also based on the results of interviews between researchers and teachers in the field of study. information was obtained that the teacher had never combined Islamic nuances with the material being taught. Therefore, we need a solution by making a teaching material in the form of an Islamic e-module. The purpose of this study was to analyze the need for an e-module with Islamic nuances by integrating Islamic values in it for class XI MA students. The research method used is descriptive qualitative method. The subjects of this study were mathematics teachers at MAN 3 Pekanbaru and class XI students at MAN 3 Pekanbaru. Analysis of research data using the Miles-Huberman Interactive Analysis which includes data reduction, data presentation, and making conclusions. The results obtained in this study are that it is necessary to develop teaching materials in the form of e-modules with Islamic nuances for class XI MA matrix materials. This research can be used as a needs analysis in research on the development of Islamic E-Modules in the XI MA class matrix material. The population used for this study is still on a small scale, therefore in future research it is hoped that it can increase the number of population used, so that it will approach the picture of the actual condition.